2020
DOI: 10.1007/s12231-020-09496-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Trait Preferences for Banana Cultivation and Use in Sub-Saharan Africa: A Literature Review1

Abstract: Understanding trait preferences of different actors in the banana value chain may facilitate the selection and adoption of new cultivars. We systematically reviewed the scholarly and gray literature on banana trait preferences, with specific attention to studies that document gender-differentiated traits. Of 44 publications reviewed, only four reported gender-specific trait preferences, indicating a significant gap in the literature. The review found that banana farmers, irrespective of gender, value similar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 35 publications
(43 reference statements)
7
49
0
Order By: Relevance
“…In contrast, hybrids were not mentioned in Osun, but community members explained that varieties referred to as agric simply means the plantain produces well. The limited use of improved varieties often linked to inferior fruit quality characteristics justifies the recent interests and emphasis in incorporating consumption attributes early in the breeding programme (Marimo et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, hybrids were not mentioned in Osun, but community members explained that varieties referred to as agric simply means the plantain produces well. The limited use of improved varieties often linked to inferior fruit quality characteristics justifies the recent interests and emphasis in incorporating consumption attributes early in the breeding programme (Marimo et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, breeders have developed and distributed high yielding disease‐resistant plantain varieties, but adoption rates have been limited (Eriksson et al ., 2018; Tenkouano et al ., 2019). Similar to other bananas, plantain production is still dominated by farmer preferred local varieties, principally owing to their consumer‐preferred attributes (taste, texture, colour and aroma; Ortiz & Swennen, 2014; Marimo et al ., 2020). Food uses of plantain in Nigeria include dodo (fried ripe pulp), boli (roasted unripe–ripe pulp), fufu (boiled and pounded unripe pulp ), amala (unripe pulp milled into flour and reconstituted into a thick dough), moin‐moin (unripe–ripe pulp milled and steamed), porridge/pottage (unripe pulp boiled with additional ingredients), chips (fried unripe pulp) and dodo Ikire (fried overripe pulp with additional ingredients; Ogazi, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…(2003); and Wale (2012), reported that varieties that lack farmer demanded characteristics were not retained on farmers’ fields. Marimo et al ., 2020 provide a comprehensive review of studies that document banana trait preferences of various value chain actors in Sub Saharan Africa. Documentation on specific preferred quality characteristics of matooke is lacking thus making it difficult for breeders to have appropriate guidance during hybrid development and selection.…”
Section: Introductionmentioning
confidence: 99%
“…The present study provides more recent insights on preferences related to banana food products given the dynamic nature of culture, changing food habits and other emerging factors that influence use. The results from this study also add to the limited literature on gender-differentiated trait preferences for banana (Marimo et al 2019) and can be used to assess marketing opportunities for upscaling 3 Rungwe in Mbeya Region). Within each district, multi-stage random sampling of up to three subcounties/divisions, up to three parishes/wards in each sub-county/division, and two or three villages in each parish/ward was conducted.…”
Section: Introductionmentioning
confidence: 72%